The Renewed Impetus to the European Union Enlargement: An Opportunity for Closer Ties between the EU and Armenia - Garcia Cancela, Eduardo (YSU Journal of International Affairs, 2025)
Russia’s aggression against Ukraine has triggered a renewed impetus for the EU’s Enlargement Policy, which has acquired geopolitical significance with the unprecedented inclusion of three Eastern partners under this framework, together with the revitalization of negotiations with the Western Balkans. Following Aldecoa’s understanding of enlargement as a process that implies a restructuring of the EU’s political system, there is also a need to address internal reforms to accommodate this new wave of accession. The consideration of Georgia, Moldova and Ukraine as candidate countries has changed the raison d’être of the European Neighborhood Policy (ENP). Originally conceived for states without clear prospects of EU integration, the ENP’s purpose has shifted, effectively opening the door for further integration of other Eastern Partnership countries into the European Union. In this context, Armenia is enhancing its relations with the EU, seeking closer integration, and even sparking debates in the country about formally requesting membership. Major challenges ahead may include the need to consolidate democracy, reverse its economic and military integration with Russia, and reach a peace agreement with Azerbaijan over Nagorno-Karabakh.